2017
DOI: 10.1111/apha.12996
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the EGF receptor in vascular smooth muscle cells prevents chronic angiotensin II‐induced arterial wall stiffening and media thickening

Abstract: Vascular smooth muscle cell-EGFRs are relevant for pathological AII action in vivo. Our data show in vivo and ex vivo the necessity of VSMC-EGFR for AII-induced structural and functional vascular remodelling, not including endothelial dysfunction. Hereby, VSMC-EGFR gains importance for complete AII-induced renal end-organ damage succeeding vascular remodelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 65 publications
(101 reference statements)
1
44
0
Order By: Relevance
“…In contrast to the above mentioned studies, we could not observe an increase in miR-221 or miR-222 in cardiac fibroblasts of mice with genetic heart hypertrophy. This might be due to the fact that in our mouse models, no signs of heart failure could be observed, e.g., lung weight per tibia length, a measure for lung congestion, was not altered [17,42].…”
Section: Discussionmentioning
confidence: 87%
“…In contrast to the above mentioned studies, we could not observe an increase in miR-221 or miR-222 in cardiac fibroblasts of mice with genetic heart hypertrophy. This might be due to the fact that in our mouse models, no signs of heart failure could be observed, e.g., lung weight per tibia length, a measure for lung congestion, was not altered [17,42].…”
Section: Discussionmentioning
confidence: 87%
“…EGFR activation has been implicated in vascular remodelling in mice infused with AngII [32,33]. Deletion of EGFR in vascular smooth muscle cells prevents AngII-induced vascular remodelling [34], while pharmacological inhibition of EGFR limits development of experimental AAA [31]. It has been previously reported that plasma kallikrein stimulates ADAM-17 activity in vascular smooth muscle cells via a bradykinin-independent mechanism involving EGFR activation and EGFR-dependent Erk1 signalling [35].…”
Section: Discussionmentioning
confidence: 99%
“…Further, they evaluate the expression of a number of genes related to fibrotic reactions and measure aortic media thickness as well as dynamic parameters such as potassium‐induced constriction of the arteries. The authors conclude from their results that vascular smooth muscle cell‐EGFRs are relevant for pathological angiotensin II action in vivo with respect to renal end‐organ damage …”
mentioning
confidence: 94%
“…Inducible knock out models have been proven to be a valuable tool in cardiovascular research. In a work by Schreier et al, the role of a deletion of the epidermal growth factor (EGF) receptor in vascular smooth muscle cells is investigated in detail. In the work, the authors evaluate the relevance of this protein during chronic angiotensin II challenge.…”
mentioning
confidence: 99%